Brain functional connectivity at rest as similarity of neuronal activities. Issue 3 (March 2016) - Tecchio, F.; Bruni, V.; Pascarella, A.; Cottone, C.; Cancelli, A.; Vitulano, D.
Abstract : The brain is a connected network, requiring complex-system measures to describe its organization principles. Here, we aim at testing whether the normalized compression distance (NCD) is a suitable quantifier of the functional connectivity between cortical regions, studied non-invasively by magnetoencephalography (MEG) in healthy people. We used the Functional Source Separation (FSS) algorithm to identify functionally homologous areas in the two hemispheres devoted to the somatosensory hand representation (FS_S1). We calculated NCD between the left and right FS_S1s at rest. NCD between the left and right FS_S1 of the same person was smaller than across different subjects ( p  < 10 −7 consistently). NCD was smaller within the left dominant hemisphere than within the nondominant right one ( p  = 3·10 −7 ) and it became more variable in older than younger people ( p  = .01). NCD measures the similarity of neuronal source activities via the signal compression length. NCD has properties expected for brain functional connectivity: within- is higher than between-subjects, in the dominant area is higher than in the non-dominant one, and it depends on age. NCD seems a good candidate for future studies on functional brain connectivity, able to overcome the limitations intrinsic to the classical Fourier or autoregressive estimates in assessing dynamics' properties of the neuronal activity.